Underreporting of Gender-Based Violence in Kerala, India : An Application of the List Randomization Method - Joseph, George; Javaid, Syed Usman; Andres, Luis Alberto; Chellaraj, Gnanaraj; Solotaroff, Jennifer L.; Rajan, S. Irudaya (World Bank, Washington, DC, 2017)
This paper analyzes the incidence and extent to which domestic violence and physical harassment on public/private buses is underreported in Kerala, India, using the list randomization technique. The results indicate that the level of underreporting is over nine percentage points for domestic violence and negligible for physical harassment on public/private buses. Urban households, especially poor urban households, tend to have higher levels of incidence of domestic violence. Further, women and those who are professionally educated tend to underreport more than others. Underreporting is also higher among the youngest and oldest age cohorts. For physical harassment on public/private buses, rural population -- especially the rural non --poor and urban females—tend to underreport compared with the rural poor and urban males.